Youth Patriotism-A Guarantee of Security and Stability - Askar Anvarov (Zien Journals, 2022)
Military servicemen of the Armed Forces of the Republic of Uzbekistan "on August 4, 2018 of the president of the Republic of Uzbekistan the adoption of the concept of educating young people in the spirit of military patriotism on the implementation of the PP-3898-th decision " on the radical improvement of the system of raising the spiritual and educational level, the work carried out in cooperation with local government bodies to ensure army and people's unity provides an opportunity to fill the ranks of our national army with young people with strong will, active civil position
Keywords: Military servicemen; civil; provides; government